Alterations in human intestinal microflora during experimental diarrhoea. Issue 1 (January 1970) - Gorbach, S. L.; Neale, G.; Levitan, R.; Hepner, G. W.
Abstract : Large quantities of fluid administered through an intestinal tube caused alterations in small bowel bacteriology in four of seven subjects. In two normal individuals, colonic bacteria were found after fluid infusion in areas of the small bowel which previously had none. The faecal microflora was also altered by the fluid purge: anaerobes were reduced in some subjects and large numbers of Enterobacter species emerged in others. In a patient with pancreatic insufficiency and diarrhoea, the concentration of Enterobacter in the faeces was directly related to the number of bowel motions per day. Treatment with pancreatic enzymes curtailed the diarrhoea and markedly reduced these organisms. Intubation showed that Enterobacter were harboured in the small intestine and suppressed in the large bowel during periods of normal bowel action. Diarrhoea caused by pancreatic enzyme withdrawal or fluid purgation removed the colonic inhibition and allowed these organisms to appear in the faeces. Acidic diarrhoea induced by lactose feeding to three hypolactasic patients caused reductions in the numbers of E. coli in the stool but increases in Enterobacter species. Bacteroides also declined in one subject. Certain alterations in small and large bowel bacteriology observed in these forms of experimental diarrhoea have also been described in naturally occurring diarrhoea of diverse aetiologies.